PERLINDUNGAN PENDUDUK SIPIL PADA KONDISI PERANG MENGGUNAKAN CLUSTER BOMBS DAN KAITANNYA DENGAN TEORI JUST WAR - Yelischa Felysia Sabrina Pane; Ida Bagus Sutama (Kertha Negara : Journal Ilmu Hukum, 2014)
Dynamic development of weapons technology has an impact on the revolution weaponry. Weapons used by early humans have changed thye system to automatic weapons with a high degree precision. It’s just that technology still has shortcomings in it’s use. Cluster bombs, a weapon that has the ability to spread in the form of a small bomb, bringing a new threat to civilians. Although the Geneva Conventions have already provide clear rules for the conduct of war based on the theory of Just War.